Pi calculating based on grid computing - Ai Wa, Wong
Nowadays computer technology is moving towards aggregating numerous compute resources (from mainframes to desktops) and abstracting them into a single,unified resource that provides a pool of compute power.Grids computing apply this concept to form a virtual computer resource to compute the task of complex scientific problem such as calculating the value of Pi in Mathematic in a short respond time. This project of calculating the value of Pi:in Mathernatic is developed using a.NET based grid computing application middleware which is Aichemi and is written using C# programming language. The result of this development is to compute the value of Pi in Mathematic in a very short respond time where meet the goal of grid computing to moveresponse times from days to hours/minutes/seconds.